Stock Volatility, Cash Flow, and Financial Planning of Sharia Securities Issuers: An ARIMA Approach - Hariyanti; Sukistanto; Febi Yanne Mustika (Universitas Islam Darul 'ulum Lamongan, 2026)
This study examines the effect of stock price fluctuations on cash flow conditions and financial planning strategies among companies listed on the Indonesia Stock Exchange’s Sharia Securities List (DES). Using a quantitative approach that combines explanatory research and time series analysis, the study analyzed 45 issuers consistently listed on the DES from 2021 to 2025. The sample was selected through purposive sampling, using secondary data from daily stock price movements and annual financial reports published by the IDX and the Financial Services Authority (OJK). ARIMA modeling was applied to forecast stock volatility, while panel data regression was used to assess its impact on internal financial conditions. The findings indicate that stock price fluctuations have a significant negative effect on operational cash flow (coefficient -12.456; p=0.007). In response to increased uncertainty, firms tend to raise their cash reserve ratio (coefficient 0.008; p=0.045), although earnings forecast accuracy declines (coefficient -0.234; p=0.003). The ARIMA (1,1,1) model produced strong predictive accuracy, with a MAPE of 3.80%. Overall, the results suggest that ARIMA-based forecasting should be integrated into scenario-based financial planning to support more adaptive managerial decisions.